2020
DOI: 10.22515/shirkah.v5i2.323
|View full text |Cite
|
Sign up to set email alerts
|

How Ramadan and Global Pandemic Affect Religiosity and Donating Behaviors

Abstract: Ramadan in the year of 2020 is the witness of global pandemic caused by the spread of Covid-19 that significantly alters human behaviors. In response to the current phenomenon, the present study is conducted to scrutinize how the holy month of Ramadan and global pandemic affect human religiosity and donating behaviors. To this end, this study employed a web-based questionnaire to gather the required data from 128 Indonesians who were voluntarily participated upon invitation. Using WarpPLS to analyze the data, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
0
3
1
3
Order By: Relevance
“…Research conducted by Wadi and Nurzaman (2020) also determined that individuals can only participate in waqf on a particular platform if they know the details of the specific waqf program and their religiosity level. This is different from previous studies, which have found that religiosity is an essential factor in Muslims' intention to donate, including cash waqf contributions (Fahrullah et al, 2020;Hiyanti et al, 2020;Johari et al, 2015;Kasri & Chaerunnisa, 2020;Syafira et al, 2020). Their findings are different to this study due to the differences in the main object.…”
Section: Impact Of Religiosity Perceived Usefulness and Intention To ...contrasting
confidence: 99%
“…Research conducted by Wadi and Nurzaman (2020) also determined that individuals can only participate in waqf on a particular platform if they know the details of the specific waqf program and their religiosity level. This is different from previous studies, which have found that religiosity is an essential factor in Muslims' intention to donate, including cash waqf contributions (Fahrullah et al, 2020;Hiyanti et al, 2020;Johari et al, 2015;Kasri & Chaerunnisa, 2020;Syafira et al, 2020). Their findings are different to this study due to the differences in the main object.…”
Section: Impact Of Religiosity Perceived Usefulness and Intention To ...contrasting
confidence: 99%
“…Sebagai negara mayoritas muslim nomor satu di dunia, Indonesia selain memiliki banyak masjid dan mushalla, juga memiliki ratusan Organisasi Pengelola Zakat (OPZ): BAZ, LAZ, UPZ di seluruh kabupaten/kota yang kehadirannya makin dipercaya publik sebagai pilihan tempat untuk membayar zakat, infak dan sedekah (Fahrullah et al, 2020). Hal tersebut setidaknya dapat dilihat dari jumlah ZIS yang terus meningkat setiap tahunnya.…”
Section: Pendahuluanunclassified
“…Perkembangan dalam aspek penghimpunan dan perubahan perilaku berdonasi masyarakat Indonesia pun makin terlihat, pasca Covid-19 menyebar ke seluruh penjuru dunia. Fahrullah et al, (2020) membuktikan, tahun 2020 lalu menjadi saksi betapa pandemi global yang disebabkan oleh penyebaran Covid-19 secara signifikan mengubah perilaku donasi. Meski kondisi sulit akibat pandemi Covid-19 dirasakan banyak pihak, ternyata masih banyak orang yang memiliki empati, bahkan tidak sedikit orang menjadikan kesempatan ini untuk membantu orang lain.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Research findings conducted by Fahrullah et.al, showed that the global pandemic situation influenced the level of community diversity and significantly affected the Muharrik: Jurnal Dakwah dan Sosial-Vol.4, No.01, (2021), pp.377-394, DOI: 10.37680/muharrik.v4i02.1082 growth of donation institutions (Fahrullah et al, 2020). Campaigns on fundraising and people's behavior in donating have grown since the pandemic entered Indonesia.…”
Section: Introductionmentioning
confidence: 99%